DUNIA HORIZONTAL DAN DUNIA VERTIKAL DALAM SUPER HILANG, SEGEROBAK SAJAK HAMID JABBAR SUATU TINJAUAN STRUKTURALISME SEMIOTIK - Thahar, Harris Effendi (Diksi, 2008)
This article aims at revealing expression of social protest as a horizontalworld and religious expression as a vertical one in the anthology of poems SuperHilang by Hamid Jabbar. By means of a structural semiotic approach, it is revealedthat the poems gathered in the anthology constitute poems which are heavy withexpression of social protest and simultaneously heavy with religious expression. Itindicates that they are poems expressing the horizontal world of the poet as a partof his society and the vertical world of the poet as a helpless being in the presenceof God.Keywords: horizontal world, vertical world, anthology, poem, semioticstructuralism